Evaluation of acetochlor-containing herbicide programs in imidazolinone- and quizalofop-resistant rice. (August 2019) - Norsworthy, Jason K.; Fogleman, Michael; Barber, Tom; Gbur, Edward E.
Abstract: Few effective management strategies remain for controlling herbicide-resistant Echinochloa crus-galli (L). Beauv. In midsouthern USA rice production. Repeated use of the same herbicide site of action (SOA) is ineffective and may be overcome by targeting alternative SOAs. At relatively low risk for evolution of resistance, very-long-chain fatty acid (VLCFA)-inhibiting herbicides (WSSA Group 15) such as acetochlor are promising candidates for weed control in rice. Field experiments were conducted in 2016 and 2017 to evaluate the impact of acetochlor formulated as Warrant ® on E. crus-galli control as part of a complete herbicide program in both imidazolinone- (Clearfield) and quizalofop- (Provisia) resistant rice systems. These studies were designed as a randomized complete block with a nontreated, weedy check included for comparison. In the Clearfield experiment, acetochlor at 1, 050 or 1470 g ai ha −1 or clomazone at 336 g ai ha −1 was applied delayed preemergence (DPRE) 1) alone, 2) followed by imazethapyr at 70 g ai ha −1 early-postemergence (EP), or 3) followed by imazethapyr EP followed by imazethapyr pre-flood (PREFLD). Herbicide treatments were identical in the Provisia experiment, with the exception being that quizalofop at 120 g ai ha −1 was applied postemergence (POST) instead of imazethapyr. Rice injury was <15% following all DPRE applications in two of the three site-years; however, rainfall events shortly after application resulted in more severe rice injury 2 WAT in 2017, particularly following acetochlor applications (49–78%). Overall, clomazone-containing programs provided superior E. crus-galli control throughout the season and rice yielded higher in clomazone-than acetochlor-containing programs. Oftentimes, clomazone- and acetochlor-containing programs were comparable within single- and multi-pass programs; however, the success of acetochlor-containing programs was more affected by rainfall and dependent on POST herbicides. Should acetochlor be labeled for use in rice, it should be applied EP followed by sequential POST applications to provide weed control and yield comparable to standard programs used today. Highlights: Clomazone-containing programs provided superior E. crus-galli control over acetochlor programs in dry-seeded rice. Rice yielded higher in clomazone- than acetochlor-containing programs because of early-season interference from E. crus-galli . Acetochlor should be applied sequentially postemergence to provide weed control and rice yield comparable to standard programs.